2004
DOI: 10.1159/000081850
|View full text |Cite
|
Sign up to set email alerts
|

Resumption and Maintenance of Employment after a First Acute Myocardial Infarction: Sociodemographic, Vocational and Medical Predictors

Abstract: In a community cohort of 833 women and men aged <60 years, employed at the time of a first acute myocardial infarction (AMI), the relation of sociodemographic, vocational, and medical variables to the following three aspects of employment was investigated longitudinally: resumption of employment anytime within 5 years after AMI, resumption of employment within 3 months of the AMI, and maintenance of employment 5 years after AMI. Different sets of characteristics of persons with a first AMI were related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 71 publications
2
16
2
2
Order By: Relevance
“…A . A weak positive relation has been shown between gender (female versus male) and work disability (30)(31)(32)(33)(34)47), (30)(31)(32)(33)(34)47), , while a weak negative relation was found between ethnic origin (white versus non-white), socioeconomic status (high versus low) and work disability (32, 58 and 46, 49, respectively). .…”
Section: Activity Limitations and Participation Restrictionsmentioning
confidence: 95%
See 3 more Smart Citations
“…A . A weak positive relation has been shown between gender (female versus male) and work disability (30)(31)(32)(33)(34)47), (30)(31)(32)(33)(34)47), , while a weak negative relation was found between ethnic origin (white versus non-white), socioeconomic status (high versus low) and work disability (32, 58 and 46, 49, respectively). .…”
Section: Activity Limitations and Participation Restrictionsmentioning
confidence: 95%
“…The level of somatic complaints was found to have a positive relation with work disability in three articles (19,28,50), while two articles found no effect (19,46). For employees with IHD, Q wave in cases with acute myocardial infarction (yes versus no) (34,51) and chest pain (yes versus no) (32,52,53) were found to be moderate positive prognostic factors for work disability. The presence of dyspnea (no versus yes) (33,53) and left ventricular function (normal versus abnormal) (19,31) have been shown to be moderate negative prognostic factors for work disability.…”
Section: Prognostic Factors For Work Disabilitymentioning
confidence: 96%
See 2 more Smart Citations
“…Several studies have investigated the health-related qua lity of life (HRQL) after cardiac interventions [10][11][12][13]. Most of these studies have found that predictors of HRQL after a heart surgery or coronary angioplasty were primarily psychological and not related to the illness severity [13][14][15][16]. Instead, research on professional life and work reintegration after cardiac interventions have focused mainly on the identification of factors predicting RTW (i.e., working/not working) or time for RTW [3,4,[17][18][19], while very few studies have investigated the quality of work resumption, in terms of a patient's job satisfaction and re-adaptation to work [15][16][17][18][19][20][21][22].…”
Section: Methodsmentioning
confidence: 99%